Evaluation of fracture resistance of zirconia monolithic restorations: an in vitro study - Arafa, Ahmed Mohamed; El-Kouedi, Ahmad; Hamza, Tamer; Katamish, Hisham (Brazilian Dental Science, 2021)
Objective: The aim of the study was to evaluate fracture resistance of zirconia monolithic restorations after ageing procedures. Material and methods: The fracture resistance of zirconia-based restoration after ageing procedures was evaluated. Monolithic translucent zirconia 3-unit FDPs were fabricated using Cerec inLab CAD/CAM system on 2 stainless steel dies prepared from stainless steel with a uniform 120 degrees circumferential deep chamfer finish line of 1 mm width and were placed into a stainless steel holder. FDPs were divided into 2 groups, the first group (Group A) was subjected to aging procedures in an autoclave at hydrothermal conditions 134 °C /2 bars for 5 hours. The second group (Group B) was not subjected to any ageing procedures and was designed as control group. All specimens of group A (Aged TZI) and group B (non- aged TZI) were loaded compressively in a universal testing machine at cross head speed 0.5 mm/min until fracture occurred. The percentage of monoclinic (m) phase was detected by XRD device. Scanning electron microscope (SEM) was used to examine the fractured surfaces for Aged TZI (Group A) and Non-aged TZI (Group B). Student’s t-test was used to compare between fracture resistances of both groups. The significance level was set at P ? 0.05. Results: The fracture resistance mean (SD) values of non-aged TZI (Group B) was 2406.9±306.8 N which showed statistically significantly higher than that of aged group (Group A) which was 1964.5±234.5 N. The percentage of monoclinic (m) phase detected by XRD device software in non-aged TZI (Group B) was nearly 0 weight % and in aged TZI (Group A) was about 42 weight %. Conclusion: Accelerated artificial aging decreases the fracture resistance of monolithic TZI FDPs.KeywordsArtificial aging; Fracture resistance; Monolithic zirconia.